2013
DOI: 10.1002/jbm.a.35030
|View full text |Cite
|
Sign up to set email alerts
|

Photofunctionalization increases the bioactivity and osteoconductivity of the titanium alloy Ti6Al4V

Abstract: This study examined the effect of photofunctionalization on bioactivity and osteoconductivity of titanium alloy Ti6Al4V. We also tested a hypothesis that the effect of photofunctionalization is as substantial as the one of surface roughening. Two different surface morphology, a roughened surface (sandblasted and acid-etched surface) and relatively smooth surface (machined surface), was tested. Ti6Al4V samples were photofunctionalized with UV light for 15 min using a photo device. Photofunctionalization convert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 55 publications
(117 reference statements)
0
61
1
1
Order By: Relevance
“…Previous studies reported that photofunctionalisation of Ti and Ti6Al4V surfaces enhanced attachment, spread, proliferation, and differentiation of osteoblasts in vitro . 3,13 The present study suggests that photofunctionalisation enhances the bioactivity and osteoconductivity of both surfaces. Notably, the BIC ratios were similar between the UV-treated groups at two weeks and control groups at four weeks, clearly demonstrating an acceleration of osseointegration.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…Previous studies reported that photofunctionalisation of Ti and Ti6Al4V surfaces enhanced attachment, spread, proliferation, and differentiation of osteoblasts in vitro . 3,13 The present study suggests that photofunctionalisation enhances the bioactivity and osteoconductivity of both surfaces. Notably, the BIC ratios were similar between the UV-treated groups at two weeks and control groups at four weeks, clearly demonstrating an acceleration of osseointegration.…”
Section: Discussionmentioning
confidence: 50%
“…17-19 The results of Ti6Al4V in this study are similar to those in previous reports. 3,5,13 The previous studies indicated that there were no differences in surface morphology before and after UV irradiation. 3,20 This study suggests that the carbon deposition on the Ti and Ti6Al4V surfaces was removed after UV irradiation, increasing the hydroxyl groups and hydrophilicity on both surfaces.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We then sterilised them using ethylene oxide (EO) gas at a temperature of 55 °C for 1 h 24, 25 . The prepared titanium discs were fully aged by storing in sealed 12-well cell culture plates under dark ambient conditions at room temperature for at least 8 weeks 26, 27 . After the end of the aging period, we divided the titanium samples into three groups for further processing:

Immediately: The titanium specimens were irradiated by UV under ambient conditions.

…”
Section: Methodsmentioning
confidence: 99%